2014
DOI: 10.2337/dc14-0008
|View full text |Cite
|
Sign up to set email alerts
|

Youth Overweight and Metabolic Disturbances in Predicting Carotid Intima-Media Thickness, Type 2 Diabetes, and Metabolic Syndrome in Adulthood: The Cardiovascular Risk in Young Finns Study

Abstract: OBJECTIVEOur objective was to assess cardiovascular risk and metabolic complications in adulthood in subjects with or without overweight and metabolic disturbances (i.e., elevated blood pressure, glucose, triglycerides, low HDL cholesterol, and high LDL cholesterol) and their combinations as youth. RESEARCH DESIGN AND METHODSUsing data from the population-based Cardiovascular Risk in Young Finns study, we examined the utility of four age-and sex-specific youth phenotypes (group I: normal weight, no metabolic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 37 publications
4
52
0
Order By: Relevance
“…Metabolically healthy obesity in young adults, in contrast, may consist of a more heterogeneous population that includes both obese subjects who are likely to develop various metabolic abnormalities in the near future as well as those who will maintain their metabolic health for several decades. In support of this concept, a recent study from the Young Finns cohort describing 34 cases of type 2 diabetes among young adults demonstrated that overweight at youth is a risk factor for diabetes, even in the absence of any metabolic abnormalities (23).…”
Section: Discussionmentioning
confidence: 70%
“…Metabolically healthy obesity in young adults, in contrast, may consist of a more heterogeneous population that includes both obese subjects who are likely to develop various metabolic abnormalities in the near future as well as those who will maintain their metabolic health for several decades. In support of this concept, a recent study from the Young Finns cohort describing 34 cases of type 2 diabetes among young adults demonstrated that overweight at youth is a risk factor for diabetes, even in the absence of any metabolic abnormalities (23).…”
Section: Discussionmentioning
confidence: 70%
“…Fifth, the mean age of incident diabetes in our cohort was around 40 years; thus it is not clear if our results are valid for other cohorts with an older age of diabetes onset. However, in several recent studies from U.S. and European cohorts, similar incident rates and a similar age of onset were reported (35)(36)(37)(38), thereby likely making our results applicable to a wide population of young adults. Finally, the use of a general intelligence test cannot be used to assess the relationship between specific cognitive domains and diabetes.…”
Section: Discussionmentioning
confidence: 90%
“…These data also includes information on reimbursement decisions for hypertension (systolic BP Ն 160 mmHg and/or diastolic BP Ͼ 95 mmHg persistently during a 6-month follow-up period with nonmedical treatment) and type 2 diabetes (fasting plasma glucose Ն 7 mmol/l, nonfasting plasma glucose Ն 11.1 mmol/l and/or GHbA1c Ն 6.5% in two different measurements) made by the Social Insurance Institution of Finland based on applications from medical practitioners. Participants were classified as having type 2 diabetes if they had: (1) a fasting plasma glucose Ն 7.0 mmol/l, (2) GHbA1C Ն 6.5%, (3) reported receiving oral hypoglycemic agents and/or insulin injections and did not have type 1 diabetes, (4) reported a history of physician diagnosed type 2 diabetes, or (5) had a medication reimbursement decision for type 2 diabetes (18). Hypertension was defined by reimbursement decision data and dyslipidemia by purchases of statins or etsetimibe.…”
Section: Classification Of Adulthood Outcomesmentioning
confidence: 99%